The role of melatonin in regulating sleep wake disorders in children attending the developmental pediatrics outpatient service of a tertiary care hospital in South India - Thampy, Megha; M. C. Mathew; Mathew, Anna; Kurien, Liya Grace; Michael Raj, John (International Journal of Contemporary Pediatrics, 2023)
Background: We have observed that 75% of children with neurodevelopmental challenges visiting the Developmental Pediatrics department of this institution have sleep wake disorders. Disturbed sleep has a negative effect on learning and behavior. In this study we assessed the effectiveness of melatonin in improving sleep wake disorders in children with developmental compromise from this south Indian state. Methods: Children with developmental challenges having sleep wake disorders confirmed by the pediatric insomnia severity index PISI, who were prescribed a daily dose of 3mg of melatonin participated in this prospective, observational, longitudinal study if the parents gave written informed consent. Parents were educated in the practice of sleep hygiene. The sleep disturbance scale for children (SDSC) was used to assess the overall pattern of sleep and six common disorders before and three weeks after starting melatonin. Results: Based on the PISI scores, 13, 58 and 20 children had mild, moderate and severe insomnia respectively. Melatonin improved sleep latency, increased duration of sleep, decreased night awakenings, crying spells, dreams and daytime drowsiness. There was a significant improvement in the sleep pattern as indicated by better scores in the total SDSC score as well the scores for the six sleep disorders (p<0.001). Conclusions: Melatonin has a significant role to play in regulating duration and quality of sleep and improving sleep pattern in developmentally challenged children with sleep-wake disorders.